The Current Immunoassays and Emerging Immunogenomic Approaches for Immunomonitoring Cancer and Infectious Diseases - Xi, Zhang; Yan, Wang; Qin, Ouyang; Hara, Levy (Journal of Cancer Genetics And Biomarkers, 2019)
As remarkable advances have been made in immunotherapies, the overall goal of immunotherapy has become the selection of patients and evaluating the benefits of treatment. One of the major obstacles to develop immunotherapies is the lack of effective immune monitoring. Monitoring of key changes in the immune system during immunotherapy (immunomonitoring) provides important insights into efficacy as well as the immune mechanisms of response at the molecular and cellular levels. Immunomonitoring techniques include traditional immunoassays that use specific antibodies to recognize the analytes of interest, new high-throughput immunoassays that target immune cells and nucleic acids, and less classical immunogenomic approaches that rely on genome-wide profiling and computational analysis on various types of clinical samples. Substantial progress has been made in the application of immunomonitoring strategies to pre-clinical and clinical studies, especially for patients with cancer and infectious diseases. Current and emerging immunoassays performed in clinical practice will be examined herein, and immunogenomic approaches that complement these techniques will be highlighted and compared with traditional methods. Finally, we will discuss several new computational methods for analyzing gene signatures for immunomonitoring, including gene expression data profiling by microarray, the nCounter technique, regular RNA-seq, and single-cell RNA-seq. Novel immunomonitoring techniques, especially immunogenomic approaches, will continue to be developed to facilitate assessment of immunotherapeutic response and predict patient outcomes in cancer and infectious disease.
Keywords: immunomonitoring; immunogenomics; cancer; infectious disease